Mycobacterium tuberculosis Virulent Factor ESAT-6 Drives Macrophage Differentiation Toward the Pro-inflammatory M1 Phenotype and Subsequently Switches It to the Anti-inflammatory M2 Phenotype - Refai, Amira; Gritli, Sami; Barbouche, Mohamed-Ridha; Essafi, Makram (Frontiers in Cellular and Infection Microbiology, 2018)
Tuberculosis, a human infectious disease caused by Mycobacterium tuberculosis (M.tb), is still a major cause of morbidity and mortality worldwide. The success of M.tb as a pathogen relies mainly on its ability to divert the host innate immune responses. One way by which M.tb maintains a persistent infection in a “silent” granuloma is to inhibit inflammation and induce an immunoregulatory phenotype in host macrophages (Ms). However, M.tb effectors governing the switch of Ms from the pro-inflammatory M1 to the anti-inflammatory M2 phenotype remain to be determined. The Early Secreted Antigenic Target 6kDa or ESAT-6, has been implicated in the virulence and pathogenesis of tuberculosis. Here, we investigated roles of ESAT-6 in M differentiation and polarization. We found that treatment of human monocytes with ESAT-6 did not interfere with differentiation of M1 Ms. However, ESAT-6 promoted differentiation of M0 and M2 Ms toward the M1 phenotype, as indicated by secretion of pro-inflammatory cytokines IL-6, IL-12 and TNF-, and induction of a typical M1 transcriptional signature. Interestingly, we found that ESAT-6 switched terminal full activation of M1 polarized Ms to the M2 phenotype. Indeed, in the pro-inflammatory M1 Ms, ESAT-6 was able to inhibit IL-12 and TNF- secretion and stimulate that of IL-10. Moreover, gene expression profiling of these cells showed that ESAT-6 induced downregulation of M1 M cell surface molecules CD80 and CD86, transcription factors IRF5 and c-MAF, cytokines IL-12, IL-10 and IL-6, as well as chemokines CXCL10 and CXCL1. Overall, our findings suggest ESAT-6 as being one of the effectors used by M.tb to induce the pro-inflammatory M1 phenotype at the primo-infection; a prerequisite step to promote granuloma formation and subsequently drive the phenotype switch of M polarization from M1 to M2 at a later stage of the infection. Our study improves current knowledge regarding mechanisms of virulence of M.tb and may be helpful to develop novel tools targeting ESAT-6 for a better and more efficient treatment of tuberculosis.